A high-chlorine capacity high-strength molecular sieve dechlorinating agent and preparation method thereof

By combining modified alumina nanofibers and supported copper-chromium molecular sieves, high penetration chlorine capacity, high radial crushing resistance, and low wear rate, high chlorine capacity high strength molecular sieve dechlorination agent was prepared, which solved the existing solution The problem of insufficient performance of liquid phase dechlorination agents has significantly improved the dechlorination efficiency and equipment stability.

CN118949924BActive Publication Date: 2025-01-03SHANGHAI HENGYE MOLECULAR SIEVE CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411430296.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2025-01-03
Estimated Expiration
2044-10-14

AI Technical Summary

Technical Problem

The existing liquid-phase dechlorination agent has low chlorine capacity, unsatisfactory radial crushing resistance and high wear rate, making it difficult to meet the demand for efficient removal of hydrogen chloride in reforming oils.

Method used

By combining modified alumina nanofibers and supported copper-chromium molecular sieve, high chlorine capacity with high penetration capacity, high radial crushing resistance, and low wear rate, high chlorine capacity high strength Molecular sieve dechlorination agent.

Benefits of technology

Achieved a penetrating chlorine capacity of 43.1~44.2%, a radial crushing force of 143~152N·cm-1 and an abrasion rate of 1.2~1.6%, which significantly improved the performance of the dechlorination agent, extended the service life and reduced it. Operating costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118949924B_ABST
    Figure CN118949924B_ABST
Patent Text Reader

Abstract

A high-chlorine capacity high-strength molecular sieve dechlorinating agent and a preparation method thereof, belonging to the technical field of dechlorination, the preparation method of the high-chlorine capacity high-strength molecular sieve dechlorinating agent comprises five steps of preparing modified alumina nanofibers, preparing loaded copper-chromium molecular sieves, preparing slurry, extrusion molding, and curing and roasting; the high-chlorine capacity high-strength molecular sieve dechlorinating agent obtained by the invention is in a reforming product oil with a chlorine content of about 4 μg / L and a water content of about 25 μg / L, and the temperature is controlled at 70°C, 1MPa, and a liquid space velocity of 5h ‑1 Under the condition of about 100%, the measured penetration capacity of chlorine is 43.1~44.2%, and the radial crushing resistance is 143~152N·cm ‑1 The wear rate is 1.2~1.6%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a high-chlorine capacity high-strength molecular sieve dechlorinating agent and a preparation method thereof, belonging to the technical field of dechlorination. Background Art

[0002] In the catalytic reforming process, the chlorine in the feed oil and the chlorides to maintain the acidic function of the reforming catalyst exist in the form of chloride ions after the reforming reaction, which will eventually enter the reforming oil and generate hydrogen chloride (HCl) in the acidic catalytic reaction system. The HCl in the reforming oil will not only affect the quality of the top product, but also cause corrosion to the downstream stabilization system and extraction device. Therefore, the efficient removal of HCl in the reforming oil is the key to ensuring the quality of the oil and the normal operation of the reforming process, and the development of an efficient dechlorination agent is the core of solving the above key problems.

[0003] At present, the dechlorinating agent for removing hydrogen chloride is mainly divided into two categories. One category is gas phase dechlorinating agent, which is generally operated at a higher temperature, or the raw material itself is gaseous. This type of dechlorinating agent technology is relatively mature, and the chlorine capacity of the dechlorinating agent is relatively large, generally reaching about 50%. The other category is liquid phase dechlorinating agent, i.e., a dechlorinating agent for liquid phase materials. Due to the low mass transfer rate in the liquid phase system, the application effect of the liquid phase dechlorinating agent is relatively poor, especially for the reforming product oil with a low chlorine content in the liquid phase raw material, there is no suitable liquid phase dechlorinating agent. Liquid phase dechlorinating agent is generally prepared by kneading or impregnation, and its main reactant is an oxide of an alkali metal, alkaline earth metal or transition metal that can react with HCl. For example, the oxides of Cu, Mg, Fe, and Mn are loaded onto a porous carrier by impregnation, and these oxide active components have a certain removal effect on HCl. In addition, since the diffusion resistance of HCl in the liquid phase is significantly higher than that of HCl in the gas phase, when removing HCl in the liquid phase, in addition to considering the active components, the dechlorinating agent also needs to consider the specific surface area, pore size and distribution of the carrier and other parameters. These parameters directly affect the dispersion of the active components in the dechlorinating agent, thereby affecting the contact efficiency between the dechlorinating active components and the inorganic chlorine in the reforming oil, and ultimately determine the chlorine capacity of the dechlorinating agent. In addition, the radial crushing resistance and abrasion rate of the dechlorinating agent are also crucial. If the radial crushing resistance is too low, it is easy to increase the pressure drop in the dechlorination device, which not only has the risk of damaging the device but also seriously affects the dechlorination effect. At the same time, the pulverization of the dechlorinating agent is very easy to contaminate the materials in the device. The abrasion rate is mainly related to the attenuation of the dechlorination performance and the service life of the dechlorinating agent. If the abrasion rate is too high, it will lead to frequent replacement of the dechlorinating agent and increase the operating cost of the dechlorination device.

[0004] CN104437342A discloses a high-chlorine capacity high-strength molecular sieve dechlorinating agent and its preparation method and application, which is suitable for the removal of inorganic chlorine in oil products, and is particularly suitable for the removal of hydrogen chloride in reformed oil. The carrier of the dechlorinating agent is a carbon molecular sieve, the active component is an oxide of an alkali metal and an alkaline earth metal, and the auxiliary component is copper oxide, iron oxide or zinc oxide. The specific surface area of ​​the carbon molecular sieve used in CN104437342A is not particularly ideal, resulting in the prepared dechlorinating agent having a maximum chlorine capacity of less than 33%, and the strength of the carbon molecular sieve is generally relatively low, and the stability of the long-term dechlorination process is also more easily affected.

[0005] CN117504807A discloses a macroporous liquid-phase dechlorinating agent and a preparation method and application thereof. The macroporous liquid-phase dechlorinating agent comprises the following components in parts by weight: 45-70 parts of dechlorinating active substance M modified silica gel powder; 15-25 parts of inorganic macroporous material; 15-25 parts of clay; the dechlorinating active substance M is selected from one or more of Ca, Mg, and / or Zn, Fe, and Cu elements; the dechlorinating active component is highly dispersed in water glass, and then rapidly reacted with dilute sulfuric acid to prepare micron-grade modified silica gel powder, which is then mixed with inorganic macroporous material and clay to prepare a high-activity, large-pore, large-pore liquid-phase dechlorinating agent. Since the dechlorinating active component is highly dispersed in situ, the large pore size improves liquid phase diffusion, and the large pore volume improves dechlorination capacity. The macroporous liquid phase dechlorination agent obtained in CN117504807A can only achieve a maximum chlorine penetration capacity of 35.6%. In addition, the organic matter of silica gel micropowder is used as the dechlorination active component, and its radial crushing resistance and abrasion rate are difficult to match those of inorganic substances, and its stability in use and service life are difficult to guarantee.

[0006] From the above, we can see that liquid phase dechlorination agents still have problems such as low chlorine capacity, unsatisfactory radial crushing resistance and high wear rate. Therefore, it is of great practical significance to develop a dechlorination agent with high chlorine capacity, high strength and low wear rate. Summary of the invention

[0007] In view of the deficiencies of the above-mentioned prior art, the present invention provides a high-chlorine capacity high-strength molecular sieve dechlorinating agent and a preparation method thereof, so as to achieve the following invention objectives: to prepare a liquid phase dechlorinating agent with high penetration chlorine capacity, high radial crushing resistance and low abrasion rate.

[0008] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical solutions:

[0009] A high-chlorine capacity high-strength molecular sieve dechlorinating agent and a preparation method thereof, wherein the high-chlorine capacity high-strength molecular sieve dechlorinating agent has a penetration chlorine capacity of 43.1-44.2wt% and a radial crushing resistance of 143-152N·cm -1 , the wear rate is 1.2~1.6%;

[0010] The preparation method of the high-chlorine capacity high-strength molecular sieve dechlorinating agent comprises five steps of preparing modified alumina nanofibers, preparing loaded copper-chromium molecular sieves, preparing slurry, extrusion molding, and curing and calcining;

[0011] The following are further improvements to the above technical solution:

[0012] Step 1: Preparation of modified alumina nanofibers

[0013] After drying the alumina nanofibers at 100-140° C. for 4-7 hours, the alumina nanofibers are added to a dispersion kettle, and then toluene and monoolein are added, and the dispersion rate is controlled at 7500-10000 rpm for intensive dispersion for 4-9 hours, and then the temperature is raised and kept constant at 70-90° C., and the dispersion rate is reduced to 1500-3000 rpm, and then 3-isocyanate propyl triethoxysilane is added, and the reaction is carried out under constant temperature reflux for 5-8 hours, and then the temperature is lowered to room temperature for centrifugal separation, and the obtained solid is washed with anhydrous ethanol for 3-5 times, and then placed in a vacuum oven, and dried at 50-70° C. for 4-8 hours to obtain modified alumina nanofibers;

[0014] The diameter of the alumina nanofibers is 10-100 nm, and the length is 100-400 nm;

[0015] The mass ratio of the aluminum oxide nanofibers, toluene, glyceryl monooleate, and 3-isocyanate propyltriethoxysilane is (20-50):(150-260):(1-4):(3-9).

[0016] Step 2: Preparation of loaded copper-chromium molecular sieve

[0017] The 13X molecular sieve powder was dried at 150-250°C for 5-9 hours, then cooled to room temperature in a dry environment, placed in a reactor, and then toluene was added. The stirring rate was controlled to be 500-800 rpm, and the temperature was raised and kept constant at 75-95°C. After reaching the constant temperature, γ-(ethylenediamino)propyltrimethoxysilane was added. After the reaction was stirred at a constant temperature for 5-8 hours under condensation reflux, the mixture was cooled to room temperature and filtered. The filtered solid was soaked and washed with acetone for 3-5 times, and then placed in a vacuum oven at 50-80°C and dried for 14-22 hours to obtain modified 1 3X molecular sieve powder, then add the modified 13X molecular sieve powder into the impregnation kettle, and then add a mixed aqueous solution of CuSO4 and Cr2(SO4)3, the amount added is limited to just immersing the 13X molecular sieve powder in the kettle, after standing and impregnating for 13 to 20 hours, start stirring, control the stirring rate at 150 to 450 rpm, stir for 20 to 40 minutes, stop stirring, continue to stand and impregnate for 13 to 20 hours, then filter the material, put the filtered solid into a muffle furnace, and after roasting at 180 to 250 ° C for 14 to 20 hours, obtain the loaded copper chromium molecular sieve;

[0018] The particle size of the 13X molecular sieve powder is 2-6 μm, and the internal pore size is 0.3-0.5 nm;

[0019] The mass ratio of the 13X molecular sieve powder, toluene, and γ-(ethylenediamino)propyltrimethoxysilane is (20-50):(140-220):(5-13);

[0020] The mixed aqueous solution of CuSO4 and Cr2(SO4)3 has a mass concentration of CuSO4 of 15-30wt% and a mass concentration of Cr2(SO4)3 of 15-28wt%.

[0021] Step 3: Prepare slurry

[0022] Add the modified alumina nanofibers and acetone into a double planetary mixer, control the stirring rate to 80-120 rpm, and the dispersion rate to 7000-9500 rpm. After stirring and dispersing for 3-6 hours, add the loaded copper-chromium molecular sieve, hydrotalcite, sodium bentonite, and furan resin, continue to stir and disperse for 5-9 hours, then add polysilazane, and stir and disperse for another 2-5 hours to obtain a slurry as thick as toothpaste.

[0023] The particle size of the hydrotalcite is 0.1-0.6 μm;

[0024] The particle size of the sodium bentonite is 0.3-0.8 μm;

[0025] The furan resin has a number average molecular weight of 2000-6500 g / mol and a viscosity of 30-100 mPa•s at 25° C.;

[0026] The polysilazane has a number average molecular weight of 600-1500 g / mol and a viscosity of 10-60 mPa•s at 25° C.;

[0027] The feed mass ratio of the modified alumina nanofiber, acetone, copper-chromium loaded molecular sieve, hydrotalcite, sodium bentonite, furan resin and polysilazane is (3-6):(40-70):(30-80):(1-3):(0.5-1.5):(3-7):(1-2).

[0028] Step 4: Extrusion

[0029] The slurry is injected into the extruder, and the screw speed and the diameter of the die opening of the die head are adjusted so that the diameter of the extruded nearly round particles is 6-13 mm to obtain the original particles of the dechlorination agent.

[0030] Step 5: Curing and calcining

[0031] The original particles of the dechlorinating agent are placed in a vacuum drying oven, dried at 40-60°C for 5-10 hours, placed in a room temperature environment with a relative air humidity of 45-65% for aging for 10-20 hours, and then transferred to a muffle furnace, heated from room temperature to 120-150°C at a heating rate of 0.5-2°C / min, and cured at a constant temperature for 5-9 hours, and then heated to 350-450°C at a heating rate of 1.5-3°C / min, and calcined at a constant temperature for 11-17 hours, and then naturally cooled to room temperature to obtain a high-chlorine capacity and high-strength molecular sieve dechlorinating agent.

[0032] Compared with the prior art, the present invention achieves the following beneficial effects:

[0033] 1. The present invention uses 13X molecular sieve powder to impregnate and load copper and chromium, two elements with high-efficiency dechlorination performance. Before loading copper and chromium, the internal pore surface and external surface of the 13X molecular sieve powder are modified with γ-(ethylenediamine)propyltrimethoxysilane. After modification, the internal pore surface and external surface of the 13X molecular sieve powder contain a large number of γ-(ethylenediamine) functional groups. This functional group containing both primary and secondary amine groups has a very strong negative charge because the nitrogen atom carries a lone electron pair. Therefore, the internal pore surface and external surface of the modified 13X molecular sieve powder have a very strong charge attraction effect on the positively charged copper ions and chromium ions. Therefore, the internal pore surface and external surface of the 13X molecular sieve powder can load a large number of copper ions and chromium ions. After roasting, the copper ions and chromium ions generate copper oxide and chromium trioxide, which are sintered and adhered to the internal pore surface and external surface of the 13X molecular sieve powder, so that the 13X molecular sieve powder has extremely strong dechlorination performance and extremely high penetration chlorine capacity;

[0034] 2. The modified alumina nanofibers added in the present invention, after being modified by 3-isocyanatepropyltriethoxysilane, have a large number of triethoxysilane functional groups and a small amount of isocyanate functional groups on the fiber surface. These two functional groups can improve the dispersion uniformity of the alumina nanofibers in acetone in the slurry preparation step. Secondly, in the curing and calcining step, the triethoxysilane functional groups and a small amount of isocyanate functional groups undergo hydrolysis reaction to generate active hydroxyl and carbamate groups. These two groups undergo cross-linking reaction with polysilazane and can also cooperate with the hydrolysis reaction of polysilazane itself to form active hydroxyl and carbamate groups between molecular sieve particles. Forming a dense three-dimensional cross-linked network and active polar groups on the surface of the chemically bonded molecular sieve, through the hydrolysis and cross-linking reaction of the modified alumina nanofibers and the hydrolysis and cross-linking reaction of the polysilazane itself, the molecular sieve particles and alumina nanofibers inside the dechlorinator form a dense microporous structure, which not only enhances the radial crushing resistance and wear resistance of the dechlorinator as a whole, but also increases the number and surface area of ​​the internal micropores, and improves the penetration chlorine capacity. In addition, alumina nanofibers are an alkaline substance and have a very large specific surface area. After forming a network inside the dechlorinator, it can also provide a very good dechlorination function to a large extent;

[0035] 3. The furan resin added in the present invention has two main functions. First, in the slurry preparation step, the bonding force between the materials is improved, and the molding ability of the slurry in the extrusion molding step is promoted. Second, the curing crosslinking density of the furan resin is relatively high, and the thermal decomposition rate of the cured resin formed after curing and crosslinking is relatively slow. In the curing and calcining step, after the furan resin in the slurry is cured, the furan resin cured body is slowly thermally decomposed during the calcining process to form a large number of micropores, which can effectively increase the micropore surface area inside the dechlorinating agent and increase the chlorine capacity of the dechlorinating agent.

[0036] 4. The high-chlorine capacity high-strength molecular sieve dechlorinating agent obtained by the present invention is used in the reforming oil with a chlorine content of about 4μg / L and a water content of about 25μg / L, and the temperature is controlled at 70℃, 1MPa, and a liquid space velocity of 5h -1 Under the condition of about 100%, the measured penetration capacity of chlorine is 43.1~44.2%, and the radial crushing resistance is 143~152N·cm -1 The wear rate is 1.2~1.6%. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 This is a scanning electron microscope photograph of the cross section of the high-chlorine capacity high-strength molecular sieve dechlorinating agent obtained in Example 1, magnified 5000 times;

[0038] Figure 2 This is a scanning electron microscope photograph of the cross section of the high-chlorine capacity high-strength molecular sieve dechlorinating agent obtained in Example 1, magnified 10,000 times;

[0039] Figure 3 This is a scanning electron microscope photograph of the cross section of the high-chlorine capacity high-strength molecular sieve dechlorinating agent obtained in Comparative Example 1, magnified 5000 times;

[0040] Figure 4 This is a scanning electron microscope photograph of the cross section of the high-chlorine capacity high-strength molecular sieve dechlorinating agent obtained in Comparative Example 3, magnified 5000 times;

[0041] Figure 5 This is a scanning electron microscope photograph of the cross-section of the high-chlorine capacity high-strength molecular sieve dechlorinating agent obtained in Comparative Example 3, magnified 10,000 times. DETAILED DESCRIPTION

[0042] The preferred embodiments of the present invention are described below. It should be understood that the preferred embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0043] Example 1: Preparation method of a high-chlorine capacity high-strength molecular sieve dechlorinating agent

[0044] Step 1: Preparation of modified alumina nanofibers

[0045] After drying the alumina nanofibers at 130° C. for 6 hours, the alumina nanofibers were added to a dispersion kettle, and then toluene and monoolein were added, and the dispersion rate was controlled at 9000 rpm for intensive dispersion for 8 hours, and then the temperature was raised and kept constant at 75° C., and the dispersion rate was reduced to 2000 rpm, and then 3-isocyanate propyl triethoxysilane was added, and the reaction was carried out under constant temperature reflux for 6 hours, and then the temperature was lowered to room temperature for centrifugal separation, and the obtained solid was washed with anhydrous ethanol for 4 times, and then placed in a vacuum oven, and dried at 65° C. for 5 hours to obtain modified alumina nanofibers;

[0046] The diameter of the alumina nanofiber is 50 nm and the length is 150 nm;

[0047] The mass ratio of the aluminum oxide nanofibers, toluene, glyceryl monooleate, and 3-isocyanate propyltriethoxysilane is 40:190:3:7.

[0048] Step 2: Preparation of loaded copper-chromium molecular sieve

[0049] The 13X molecular sieve powder was dried at 220°C for 6 hours, then cooled to room temperature in a dry environment, placed in a reactor, and then toluene was added. The stirring rate was controlled at 600 rpm, and the temperature was raised and kept constant at 90°C. After reaching the constant temperature, γ-(ethylenediamino)propyltrimethoxysilane was added. After the reaction was stirred at a constant temperature for 6 hours under condensation reflux, the temperature was cooled to room temperature, filtered, and the filtered solid was soaked and washed with acetone for 4 times, and then placed in a 60°C vacuum oven for 19 hours to obtain a modified 13X Molecular sieve powder, then add the modified 13X molecular sieve powder into the impregnation kettle, and then add a mixed aqueous solution of CuSO4 and Cr2(SO4)3, the amount added is limited to just immersing the 13X molecular sieve powder in the kettle, after standing and impregnating for 18 hours, start stirring, control the stirring rate at 350 rpm, stir for 35 minutes, stop stirring, continue to stand and impregnate for 17 hours, then filter the material, put the filtered solid into a muffle furnace, and roast at 200°C for 16 hours to obtain a loaded copper-chromium molecular sieve;

[0050] The particle size of the 13X molecular sieve powder is 4 μm, and the internal pore size is 0.4 nm;

[0051] The mass ratio of the 13X molecular sieve powder, toluene, and γ-(ethylenediamino)propyltrimethoxysilane is 40:200:11;

[0052] The mixed aqueous solution of CuSO4 and Cr2(SO4)3 has a mass concentration of CuSO4 of 20wt% and a mass concentration of Cr2(SO4)3 of 22wt%.

[0053] Step 3: Prepare slurry

[0054] Add modified alumina nanofibers and acetone into a double planetary mixer, control the stirring rate to 110 rpm, and the dispersion rate to 8500 rpm. After stirring and dispersing for 5 hours, add the loaded copper-chromium molecular sieve, hydrotalcite, sodium bentonite, and furan resin. Continue stirring and dispersing for 6 hours, then add polysilazane, and stir and disperse for another 3 hours to obtain a viscous slurry like toothpaste.

[0055] The particle size of the hydrotalcite is 0.5 μm;

[0056] The particle size of the sodium bentonite is 0.4 μm;

[0057] The furan resin has a number average molecular weight of 3500 g / mol and a viscosity of 50 mPa•s at 25° C.;

[0058] The polysilazane has a number average molecular weight of 1100 g / mol and a viscosity of 30 mPa•s at 25° C.;

[0059] The mass ratio of the modified alumina nanofiber, acetone, copper-chromium loaded molecular sieve, hydrotalcite, sodium bentonite, furan resin and polysilazane is 5:60:60:2:1:6:1.4.

[0060] Step 4: Extrusion

[0061] The slurry was injected into the extruder, and the screw speed and the diameter of the die of the die head were adjusted so that the diameter of the extruded nearly round particles was 8 mm, thereby obtaining the original particles of the dechlorinating agent.

[0062] Step 5: Curing and calcining

[0063] The original particles of the dechlorinating agent were placed in a vacuum drying oven, dried at 55°C for 8 hours, placed in a room temperature environment with a relative air humidity of 60% for aging for 18 hours, and then transferred to a muffle furnace, heated from room temperature to 130°C at a heating rate of 1°C / min, and cured at a constant temperature for 8 hours. Then, the temperature was increased to 400°C at a heating rate of 2°C / min, and calcined at a constant temperature for 15 hours. Then, it was naturally cooled to room temperature to obtain a high-chlorine capacity and high-strength molecular sieve dechlorinating agent.

[0064] Example 2: Preparation method of a high-chlorine capacity high-strength molecular sieve dechlorinating agent

[0065] Step 1: Preparation of modified alumina nanofibers

[0066] After drying the alumina nanofibers at 100° C. for 4 hours, the alumina nanofibers were added to a dispersion kettle, and then toluene and monoolein were added, and the dispersion rate was controlled to be 7500 rpm for intensive dispersion for 4 hours, and then the temperature was raised and kept constant at 70° C., and the dispersion rate was reduced to 1500 rpm, and then 3-isocyanate propyl triethoxysilane was added, and the reaction was carried out under constant temperature reflux for 5 hours, and then the temperature was lowered to room temperature for centrifugal separation, and the obtained solid was washed with anhydrous ethanol for 3 times, and then placed in a vacuum oven, and dried at 50° C. for 4 hours to obtain modified alumina nanofibers;

[0067] The diameter of the alumina nanofiber is 10 nm and the length is 100 nm;

[0068] The mass ratio of the aluminum oxide nanofibers, toluene, glyceryl monooleate, and 3-isocyanate propyltriethoxysilane is 20:150:1:3.

[0069] Step 2: Preparation of loaded copper-chromium molecular sieve

[0070] The 13X molecular sieve powder was dried at 150°C for 5 hours, then cooled to room temperature in a dry environment, placed in a reactor, and then toluene was added. The stirring rate was controlled to be 500 rpm, and the temperature was raised and kept constant at 75°C. After reaching the constant temperature, γ-(ethylenediamino)propyltrimethoxysilane was added. After the reaction was stirred at a constant temperature for 5 hours under condensation reflux, the temperature was cooled to room temperature, filtered, and the filtered solid was soaked and washed with acetone for 3 times, and then placed in a 50°C vacuum oven and dried for 14 hours to obtain the modified 13X Molecular sieve powder, then add the modified 13X molecular sieve powder into the impregnation kettle, and then add a mixed aqueous solution of CuSO4 and Cr2(SO4)3, the amount added is limited to just immersing the 13X molecular sieve powder in the kettle, after standing and impregnating for 13 hours, start stirring, control the stirring rate at 150 rpm, stir for 20 minutes, stop stirring, continue to stand and impregnate for 13 hours, then filter the material, put the filtered solid into a muffle furnace, and after roasting at 180°C for 14 hours, obtain the loaded copper-chromium molecular sieve;

[0071] The particle size of the 13X molecular sieve powder is 2 μm, and the internal pore size is 0.3 nm;

[0072] The mass ratio of the 13X molecular sieve powder, toluene, and γ-(ethylenediamino)propyltrimethoxysilane is 20:140:5;

[0073] The mixed aqueous solution of CuSO4 and Cr2(SO4)3 has a mass concentration of CuSO4 of 15wt% and a mass concentration of Cr2(SO4)3 of 15wt%.

[0074] Step 3: Prepare slurry

[0075] Add the modified alumina nanofibers and acetone into a double planetary mixer, control the stirring rate to 80 rpm, and the dispersion rate to 7000 rpm. After stirring and dispersing for 3 hours, add the loaded copper-chromium molecular sieve, hydrotalcite, sodium bentonite, and furan resin. Continue stirring and dispersing for 5 hours, then add polysilazane, and stir and disperse for another 2 hours to obtain a viscous slurry like toothpaste.

[0076] The particle size of the hydrotalcite is 0.1 μm;

[0077] The particle size of the sodium bentonite is 0.3 μm;

[0078] The furan resin has a number average molecular weight of 2000 g / mol and a viscosity of 30 mPa•s at 25° C.;

[0079] The polysilazane has a number average molecular weight of 600 g / mol and a viscosity of 10 mPa•s at 25° C.;

[0080] The mass ratio of the modified alumina nanofiber, acetone, copper-chromium loaded molecular sieve, hydrotalcite, sodium bentonite, furan resin and polysilazane is 3:40:30:1:0.5:3:1.

[0081] Step 4: Extrusion

[0082] The slurry was injected into the extruder, and the screw speed and the diameter of the die of the die head were adjusted so that the diameter of the extruded nearly round particles was 6 mm, thereby obtaining the original particles of the dechlorinating agent.

[0083] Step 5: Curing and calcining

[0084] The original particles of the dechlorinating agent were placed in a vacuum drying oven, dried at 40°C for 5 hours, placed in a room temperature environment with a relative air humidity of 45% for aging for 10 hours, and then transferred to a muffle furnace, and heated from room temperature to 120°C at a heating rate of 0.5°C / min. After constant temperature curing for 5 hours, the temperature was then increased to 350°C at a heating rate of 1.5°C / min, and constant temperature roasted for 11 hours. Then, it was naturally cooled to room temperature to obtain a high chlorine capacity and high strength molecular sieve dechlorinating agent.

[0085] Example 3: Preparation method of a high-chlorine capacity high-strength molecular sieve dechlorinating agent

[0086] Step 1: Preparation of modified alumina nanofibers

[0087] After drying the alumina nanofibers at 140° C. for 7 hours, the alumina nanofibers were added to a dispersion kettle, and then toluene and monoolein were added, and the dispersion rate was controlled to be 10,000 rpm, and the dispersion was vigorously dispersed for 9 hours, and then the temperature was raised and kept constant at 90° C., and the dispersion rate was reduced to 3,000 rpm, and then 3-isocyanate propyl triethoxysilane was added, and the reaction was carried out under constant temperature reflux for 8 hours, and then the temperature was lowered to room temperature and centrifuged, and the obtained solid was washed with anhydrous ethanol for 5 times, and then placed in a vacuum oven, and dried at 70° C. for 8 hours to obtain modified alumina nanofibers;

[0088] The diameter of the alumina nanofiber is 100 nm and the length is 400 nm;

[0089] The mass ratio of the aluminum oxide nanofibers, toluene, glyceryl monooleate, and 3-isocyanate propyltriethoxysilane is 50:260:4:9.

[0090] Step 2: Preparation of loaded copper-chromium molecular sieve

[0091] The 13X molecular sieve powder was dried at 250°C for 9 hours, then cooled to room temperature in a dry environment, placed in a reactor, and then toluene was added. The stirring rate was controlled to 800 rpm, and the temperature was raised and kept constant at 95°C. After reaching the constant temperature, γ-(ethylenediamino)propyltrimethoxysilane was added. After the reaction was stirred at a constant temperature for 8 hours under condensation reflux, the reaction was cooled to room temperature, filtered, and the filtered solid was soaked and washed with acetone for 5 times, and then placed in a vacuum oven at 80°C and dried for 22 hours to obtain a modified 13X Molecular sieve powder, then add the modified 13X molecular sieve powder into the impregnation kettle, and then add a mixed aqueous solution of CuSO4 and Cr2(SO4)3, the amount added is limited to just immersing the 13X molecular sieve powder in the kettle, after standing and impregnating for 20 hours, start stirring, control the stirring rate at 450 rpm, stir for 40 minutes, stop stirring, continue to stand and impregnate for 20 hours, then filter the material, put the filtered solid into a muffle furnace, and after roasting at 250°C for 20 hours, obtain the loaded copper-chromium molecular sieve;

[0092] The particle size of the 13X molecular sieve powder is 6 μm, and the internal pore size is 0.5 nm;

[0093] The mass ratio of the 13X molecular sieve powder, toluene, and γ-(ethylenediamino)propyltrimethoxysilane is 50:220:13;

[0094] The mixed aqueous solution of CuSO4 and Cr2(SO4)3 has a mass concentration of CuSO4 of 30wt% and a mass concentration of Cr2(SO4)3 of 28wt%.

[0095] Step 3: Prepare slurry

[0096] Add modified alumina nanofibers and acetone into a double planetary mixer, control the stirring rate to 120 rpm, and the dispersion rate to 9500 rpm. After stirring and dispersing for 6 hours, add the loaded copper-chromium molecular sieve, hydrotalcite, sodium bentonite, and furan resin. Continue stirring and dispersing for 9 hours, then add polysilazane, and stir and disperse for another 5 hours to obtain a viscous slurry like toothpaste.

[0097] The particle size of the hydrotalcite is 0.6 μm;

[0098] The particle size of the sodium bentonite is 0.8 μm;

[0099] The furan resin has a number average molecular weight of 6500 g / mol and a viscosity of 100 mPa•s at 25° C.;

[0100] The polysilazane has a number average molecular weight of 1500 g / mol and a viscosity of 60 mPa•s at 25° C.;

[0101] The mass ratio of the modified alumina nanofiber, acetone, copper-chromium loaded molecular sieve, hydrotalcite, sodium bentonite, furan resin and polysilazane is 6:70:80:3:1.5:7:2.

[0102] Step 4: Extrusion

[0103] The slurry was injected into the extruder, and the screw speed and the diameter of the die of the die head were adjusted so that the diameter of the extruded nearly round particles was 13 mm, thereby obtaining the original particles of the dechlorinating agent.

[0104] Step 5: Curing and calcining

[0105] The original particles of the dechlorinating agent were placed in a vacuum drying oven, dried at 60°C for 10 hours, placed in a room temperature environment with a relative air humidity of 65% for aging for 20 hours, and then transferred to a muffle furnace, and heated from room temperature to 150°C at a heating rate of 2°C / min. After constant temperature curing for 9 hours, the temperature was then increased to 450°C at a heating rate of 3°C / min, and constant temperature roasted for 17 hours. Then, it was naturally cooled to room temperature to obtain a high chlorine capacity and high strength molecular sieve dechlorinating agent.

[0106] Comparative Example 1: Based on Example 1, step 1, preparing modified alumina nanofibers, is not performed. In step 3, in preparing the slurry, 5 parts of modified alumina nanofibers are replaced with 5 parts of alumina nanofibers. The specific operation is as follows:

[0107] The step 1 of preparing modified alumina nanofibers is not performed;

[0108] The operation of step 2 is the same as that of embodiment 1;

[0109] Step 3: Prepare slurry

[0110] The modified alumina nanofibers were replaced by 5 parts of alumina nanofibers, and the other operations were the same as in Example 1;

[0111] The operations of steps 4 and 5 are the same as those of Example 1.

[0112] Comparative Example 2: Based on Example 1, step 2, preparation of the loaded copper-chromium molecular sieve, is not performed. In step 3, in the preparation of the slurry, 60 parts of the loaded copper-chromium molecular sieve are replaced with 60 parts of 13X molecular sieve powder. The specific operation is as follows:

[0113] Step 1: The operation is the same as in Example 1;

[0114] Step 2, preparing the loaded copper-chromium molecular sieve, is not performed;

[0115] Step 3: Prepare slurry

[0116] 60 parts of the loaded copper-chromium molecular sieve were replaced with 60 parts of 13X molecular sieve powder, and the other operations were the same as in Example 1;

[0117] The operations of steps 4 and 5 are the same as those of Example 1.

[0118] Comparative Example 3: Based on Example 1, in step 3, in preparing the slurry, no polysilazane was added, and 1.4 parts of polysilazane were replaced by 1.4 parts of acetone. The specific operation was as follows:

[0119] The operations of steps 1 and 2 are the same as those of Example 1;

[0120] Step 3: Prepare slurry

[0121] 1.4 parts of polysilazane were replaced by 1.4 parts of acetone, and the other operations were the same as in Example 1;

[0122] The operations of steps 4 and 5 are the same as those of Example 1.

[0123] Performance Test:

[0124] The penetration chlorine capacity of the high-chlorine capacity high-strength molecular sieve dechlorinating agent obtained in Examples 1, 2, 3 and Comparative Examples 1, 2, 3 was tested by the following test method: the reformed oil with a chlorine content of about 4 μg / L and a water content of about 25 μg / L was heated at 70°C, 1 MPa, and a liquid space velocity of 5 h -1 Under the conditions of , the dechlorinating agent is loaded to carry out the liquid phase dynamic dechlorination experiment, and the chlorine content in the reformed oil flowing out of the dechlorination tank is measured. When the chlorine content of the effluent is greater than 0.5μg / L, it can be regarded as breakthrough. According to the formula: breakthrough chlorine capacity = (mass content of chlorine in the dechlorinating agent after breakthrough) / (total mass of the dechlorinating agent after breakthrough) × 100%, the breakthrough chlorine capacity of the dechlorinating agent is obtained;

[0125] Refer to "HG / T 2782-2024 Determination of Crush Resistance of Fertilizer Catalyst Particles" to test the radial crush resistance;

[0126] Test the attrition rate according to "HG / T 2976-2011 Determination of attrition rate of fertilizer catalysts";

[0127] The specific test results are shown in Table 1:

[0128] Table 1

[0129]

[0130] From the data in Table 1, it can be seen that in Comparative Example 1 where the aluminum oxide nanofibers are not surface treated, the chlorine penetration capacity is reduced to 30.6%, and the radial crushing resistance is reduced to 107 N·cm -1, the wear rate increased to 4.1%, which indicates that the aluminum oxide nanofibers are not surface treated, and the dispersion uniformity is seriously affected, resulting in a poor effect of aluminum oxide nanofibers reinforcing the dechlorination agent, which in turn causes a significant decrease in radial crushing resistance and wear rate, among which the penetration chlorine capacity is significantly reduced. This may be because the aluminum oxide nanofibers are alkaline and have a large surface area, and have certain dechlorination properties. Uneven dispersion will lead to a decrease in the dechlorination performance of the aluminum oxide nanofibers, which in turn causes a significant decrease in the dechlorination performance of the dechlorination agent in Comparative Example 1; in Comparative Example 2, the 13X molecular sieve powder is not loaded with copper and chromium, and the radial crushing resistance and wear rate are almost the same as those in Example 1, which shows that the loading of copper and chromium has an effect on the dechlorination. The mechanical properties of the dechlorinating agent have no effect, but the penetration chlorine capacity of Comparative Example 2 is reduced by more than half compared with Example 1, which shows that the copper-chromium loaded 13X molecular sieve powder plays a decisive role in improving the dechlorination performance of the dechlorinating agent; Comparative Example 3 does not add polysilazane, and compared with Example 1, the radial crushing resistance and the wear rate are sharply reduced, which shows that polysilazane plays a vital role in improving the mechanical properties of the dechlorinating agent. In addition, the penetration chlorine capacity of Comparative Example 3 also decreases significantly, which may be because polysilazane increases the cross-linking density of the dechlorinating agent and increases the number of micropores, which has a positive effect on improving the penetration chlorine capacity. Without adding polysilazane, the reduction in the number of micropores leads to a decrease in the penetration chlorine capacity.

[0131] Attached Figure 1 and attached Figure 2 The high-chlorine capacity and high-strength molecular sieve dechlorinating agent obtained in Example 1 is shown in the electron microscope photos of its cross section magnified 5000 times and 10000 times. It can be seen that dense alumina nanofibers are attached to the surface of the molecular sieve particles, and the molecular sieve particles are also filled with a very dense and spider-web-like three-dimensional network-like material. This is a mesh mainly composed of alumina nanofibers. These meshes not only provide a large number of micropores with pore sizes in the micron and submicron levels to increase the penetration chlorine capacity, but also improve the radial crushing resistance and wear resistance of the dechlorinating agent; Figure 3 This is a scanning electron microscope photograph of the cross-section of the high-chlorine capacity high-strength molecular sieve dechlorinating agent obtained in Comparative Example 1, magnified 5000 times. Figure 3 The alumina nanofibers attached to the surface of the molecular sieve particles are very sparse, and there is no three-dimensional network-like material between the molecular sieve particles. This may be because the alumina nanofibers added in Comparative Example 1 have not been surface modified and are not evenly dispersed inside the dechlorinating agent, and then agglomerated into particles, which makes it difficult to form a network between the molecular sieve particles and to fully contact the molecular sieve surface and sinter together. When making the cross-sectional test sample, these alumina nanofibers agglomerated into particles are not effectively sintered together with the dechlorinating agent molecular sieve matrix, and fall off from the cross-sectional view of the dechlorinating agent, showing an attached Figure 3 The state shown; Figure 4 and attached Figure 5The high-chlorine capacity high-strength molecular sieve dechlorinating agent obtained in Comparative Example 3 is an electron microscope photograph of its cross section magnified 5000 times and 10000 times, and is similar to the attached Figure 1 and attached Figure 2 In comparison, Figure 4 and attached Figure 5 There are very few alumina nanofibers attached to the surface of the molecular sieve particles, and no dense network is formed between the molecular sieve particles. This may be because no polysilazane is added in Comparative Example 3, and the alumina nanofibers and the alumina nanofibers do not form effective adhesion and cross-linking, which makes it difficult to form a strong network between the molecular sieve particles of the dechlorination agent in Comparative Example 3, and it is also difficult for more alumina nanofibers to attach to the surface of the molecular sieve particles.

[0132] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for preparing a high-chlorine capacity high-strength molecular sieve dechlorinating agent, characterized in that: The preparation method of the high-chlorine capacity high-strength molecular sieve dechlorinating agent comprises five steps of preparing modified alumina nanofibers, preparing loaded copper-chromium molecular sieves, preparing slurry, extrusion molding, and curing and calcining; The modified alumina nanofibers are prepared by drying the alumina nanofibers at 100-140° C. for 4-7 hours, adding the alumina nanofibers to a dispersion kettle, then adding toluene and glyceryl monooleate, controlling the dispersion rate at 7500-10000 rpm, and strongly dispersing for 4-9 hours, then raising the temperature and keeping the temperature constant at 70-90° C., reducing the dispersion rate to 1500-3000 rpm, then adding 3-isocyanate propyl triethoxysilane, reacting for 5-8 hours under constant temperature reflux, cooling to room temperature, and centrifuging, washing the obtained solid with anhydrous ethanol for 3-5 times, and then putting it in a vacuum oven, and drying it at 50-70° C. for 4-8 hours to obtain the modified alumina nanofibers; The preparation of the loaded copper-chromium molecular sieve comprises drying the 13X molecular sieve powder at 150-250° C. for 5-9 hours, cooling it to room temperature in a dry environment, placing it in a reaction kettle, adding toluene, controlling the stirring rate at 500-800 rpm, raising the temperature and maintaining the temperature at 75-95° C., and after reaching the constant temperature, adding γ-(ethylenediamino)propyltrimethoxysilane, stirring and reacting at a constant temperature for 5-8 hours under a condensation reflux state, cooling it to room temperature, filtering, and soaking and washing the filtered solid with acetone for 3-5 times, and then placing it in a vacuum oven at 50-80° C. and drying it for 14-22 hours. , and obtain modified 13X molecular sieve powder. Then, add the modified 13X molecular sieve powder into an impregnation kettle, and then add a mixed aqueous solution of CuSO4 and Cr2(SO4)3, the amount of which is limited to just immersing the 13X molecular sieve powder in the kettle. After standing and impregnating for 13 to 20 hours, start stirring, control the stirring rate at 150 to 450 rpm, stir for 20 to 40 minutes, stop stirring, continue standing and impregnating for 13 to 20 hours, then filter the material, put the filtered solid into a muffle furnace, and roast at 180 to 250°C for 14 to 20 hours to obtain a loaded copper-chromium molecular sieve. The slurry is prepared by adding the modified alumina nanofibers and acetone into a double planetary mixer, controlling the stirring rate to 80-120 rpm and the dispersion rate to 7000-9500 rpm, stirring and dispersing for 3-6 hours, then adding the loaded copper-chromium molecular sieve, hydrotalcite, sodium bentonite, and furan resin, continuing to stir and disperse for 5-9 hours, then adding polysilazane, and stirring and dispersing for another 2-5 hours to obtain a slurry as viscous as toothpaste; The extrusion molding comprises injecting the slurry into the extruder, adjusting the screw speed and the diameter of the die of the die head so that the diameter of the extruded nearly round particles is 6-13 mm, and obtaining the original particles of the dechlorinating agent; The curing and calcining comprises placing the original particles of the dechlorinating agent in a vacuum drying oven, drying at 40-60° C. for 5-10 hours, placing the particles in a room temperature environment with a relative air humidity of 45-65% for aging for 10-20 hours, transferring the particles to a muffle furnace, heating the temperature from room temperature to 120-150° C. at a heating rate of 0.5-2° C. / min, curing the particles at a constant temperature for 5-9 hours, then heating the particles to 350-450° C. at a heating rate of 1.5-3° C. / min, calcining the particles at a constant temperature for 11-17 hours, and then cooling the particles naturally to room temperature to obtain a high chlorine capacity high strength molecular sieve dechlorinating agent.

2. The method for preparing a high chlorine capacity high strength molecular sieve dechlorinating agent according to claim 1, characterized in that: The diameter of the alumina nanofibers is 10-100 nm, and the length is 100-400 nm; The mass ratio of the aluminum oxide nanofibers, toluene, glyceryl monooleate, and 3-isocyanate propyltriethoxysilane is (20-50):(150-260):(1-4):(3-9).

3. The method for preparing a high chlorine capacity high strength molecular sieve dechlorinating agent according to claim 1, characterized in that: The particle size of the 13X molecular sieve powder is 2-6 μm, and the internal pore size is 0.3-0.5 nm; The mass ratio of the 13X molecular sieve powder, toluene, and γ-(ethylenediamino)propyltrimethoxysilane is (20-50):(140-220):(5-13); The mixed aqueous solution of CuSO4 and Cr2(SO4)3 has a mass concentration of CuSO4 of 15-30wt% and a mass concentration of Cr2(SO4)3 of 15-28wt%.

4. The method for preparing a high chlorine capacity high strength molecular sieve dechlorinating agent according to claim 1, characterized in that: The particle size of the hydrotalcite is 0.1-0.6 μm; The particle size of the sodium bentonite is 0.3-0.8 μm; The furan resin has a number average molecular weight of 2000-6500 g / mol and a viscosity of 30-100 mPa•s at 25° C.; The polysilazane has a number average molecular weight of 600-1500 g / mol and a viscosity of 10-60 mPa•s at 25° C.; The feed mass ratio of the modified alumina nanofiber, acetone, copper-chromium loaded molecular sieve, hydrotalcite, sodium bentonite, furan resin and polysilazane is (3-6):(40-70):(30-80):(1-3):(0.5-1.5):(3-7):(1-2).

5. The high chlorine capacity high strength molecular sieve dechlorinating agent obtained by the preparation method according to any one of claims 1 to 4, characterized in that: The high-chlorine capacity high-strength molecular sieve dechlorination agent has a penetration chlorine capacity of 43.1-44.2wt% and a radial crushing resistance of 143-152N·cm -1 The wear rate is 1.2~1.6%.

Citation Information

Patent Citations

  • High-chloride-capacity liquid-phase dechlorinating agent as well as preparation method and application thereof

    CN104437342A

  • Large-pore-volume liquid-phase dechlorinating agent as well as preparation method and application thereof

    CN117504807A

  • A method to prepare a high-purity high-density monocrystalline silicon nitride nano array

    CN101550600A

  • Preparation method of high-chlorine-capacity liquid-phase dechlorinating agent

    CN118634781A